Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Impact of sarcopenia and obesity on skeletal muscle size, gene expression, and mitochondrial function - Hector G. Paez; Christopher R. Pitzer; Jessica L. Halle; Peter J. Ferrandi; James A. Carson; Junaith S. Mohamed; Stephen E. Alway (GeroScience, 2025)
Skeletal muscle is a primary tissue of dysfunction during both aging and obesity. Recently, the coincidence of obesity and aging has gained attention due to the intersection of the obesity epidemic with an aging demographic. Both aging and obesity are associated with marked defects in skeletal muscle metabolic health. Despite these findings, we have a poor understanding of how obesity and aging may interact to impact skeletal muscle mass and metabolic health. Therefore, we investigated the impact of high-fat diet (HFD)-induced obesity on skeletal muscle mass, mitochondrial function, transcriptomics, and whole-body metabolism in young and aged mice. We observed main effects of diet and age on several measures of whole-body metabolic function (VO 2 , VCO 2 , and RER). Complex I-driven mitochondrial proton leak was significantly elevated by HFD-induced obesity across both age groups; however, a main effect of aging for reduced complex I leak was detected in the soleus muscle. Interestingly, aged animals fed a HFD did not exhibit lower muscle mass than chow-fed young animals, but did present with stark increases in muscle triglyceride content and a unique transcriptional response to HFD. HFD-induced obesity impacted the muscle transcriptome differently in the muscles of young and aged mice, indicating that obesity can change altered gene expression with age. Our findings suggest that the presence of obesity can both compound and counteract age-associated changes to muscle mass, gene expression, and mitochondrial function.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Rapid, complex back barrier pedestal formation preconditions washover deposition on the southeast Indian coast - Chris Gouramanis; Seshachalam Srinivasalu; Andasabari Karthik; Dat T. Pham; Stephen Carson; Adam D. Switzer (Marine Geology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The obesity-breast cancer link: a multidisciplinary perspective - Emily N. Devericks; Meredith S. Carson; Lauren E. McCullough; Michael F. Coleman; Stephen D. Hursting (Cancer and Metastasis Reviews, 2022)
Obesity, exceptionally prevalent in the USA, promotes the incidence and progression of numerous cancer types including breast cancer. Complex, interacting metabolic and immune dysregulation marks the development of both breast cancer and obesity. Obesity promotes chronic low-grade inflammation, particularly in white adipose tissue, which drives immune dysfunction marked by increased pro-inflammatory cytokine production, alternative macrophage activation, and reduced T cell function. Breast tissue is predominantly composed of white adipose, and developing breast cancer readily and directly interacts with cells and signals from adipose remodeled by obesity. This review discusses the biological mechanisms through which obesity promotes breast cancer, the role of obesity in breast cancer health disparities, and dietary interventions to mitigate the adverse effects of obesity on breast cancer. We detail the intersection of obesity and breast cancer, with an emphasis on the shared and unique patterns of immune dysregulation in these disease processes. We have highlighted key areas of breast cancer biology exacerbated by obesity, including incidence, progression, and therapeutic response. We posit that interception of obesity-driven breast cancer will require interventions that limit protumor signaling from obese adipose tissue and that consider genetic, structural, and social determinants of the obesity–breast cancer link. Finally, we detail the evidence for various dietary interventions to offset obesity effects in clinical and preclinical studies of breast cancer. In light of the strong associations between obesity and breast cancer and the rising rates of obesity in many parts of the world, the development of effective, safe, well-tolerated, and equitable interventions to limit the burden of obesity on breast cancer are urgently needed.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Natural Intertidal Oyster Reef Growth Across Two Landscape Settings and Tidal Ranges - Molly C. Bost; Antonio B. Rodriguez; Justin T. Ridge; Carson B. Miller; Stephen R. Fegley (Estuaries and Coasts, 2021)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Technological advances in maize breeding: past, present and future - Carson Andorf; William D. Beavis; Matthew Hufford; Stephen Smith; Walter P. Suza; Kan Wang; Margaret Woodhouse; Jianming Yu; Thomas Lübberstedt (Theoretical and Applied Genetics, 2019)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

A simultaneous test of trophic interaction models: which vegetation characteristic explains herbivore control over plant community mass? - James Patrick Cronin; Stephen J. Tonsor; Walter P. Carson (Ecology Letters, 2010)
Ecology Letters (2010) 13: 202–212 Abstract Predicting herbivore control over plants (i.e. changes in plant mass due to herbivore damage) is a central goal of ecology. Progress has been limited, however, because the vegetation characteristics thought to influence herbivore control are naturally correlated and typically experimentally confounded. To address this problem, we defined eight conventional models that predict herbivore control over plant community mass, each model based on a different vegetation characteristic (i.e. host concentration, tissue nitrogen, growth rate, size, tolerance of herbivory or net primary productivity). We then used structural equation modelling to test each model against two field experiments. Our results clearly rejected all models except for a tolerance of herbivory mechanism; stems with greater access to limiting resources better tolerated herbivory, regardless of where herbivore activity was greatest. Consequently, herbivore reductions of plant community mass were greatest at low resource availability. This adds to evidence that herbivore activity poorly predicts herbivore control.

Variation in RTN3 and PPIL2 Genes Does not Influence Platelet Membrane β-Secretase Activity or Susceptibility to Alzheimer’s Disease in the Northern Irish Population - Robyn Carson; Amy Jayne McKnight; Stephen Todd; Wei Wei Liu; Shirley Heggarty; David Craig; Bernadette McGuinness; G. Brent Irvine; A. Peter Passmore; Janet A. Johnston (NeuroMolecular Medicine, 2009)

Genetic Variation in the α7 Nicotinic Acetylcholine Receptor is Associated with Delusional Symptoms in Alzheimer’s Disease - Robyn Carson; David Craig; Dominic Hart; Stephen Todd; Bernadette McGuinness; Janet A. Johnston; Francis A. O’Neill; Craig W. Ritchie; A. Peter Passmore (NeuroMolecular Medicine, 2008)

Evaluating the post-release efficacy of invasive plant biocontrol by insects: a comprehensive approach - Walter P. Carson; Stephen M. Hovick; Anthony J. Baumert; Daniel E. Bunker; Thomas H. Pendergast (Arthropod-Plant Interactions, 2008)